High Performace Liquid Chromtographic Determination of Nicardipine Hydrochloride in Human Plasma - Y. S. R. Krishnaiah; V. Satyanarayana; P. Bhaskar (E-Journal of Chemistry)
A sensitive high-performance liquid chromatographic method was developed for the estimation of nicardipine hydrochloride in human plasma. Varying amount of nicardipine hydrochloride (2.5 to 150 ng/0.5 mL) and fixed quantity (100 ng/0.5 mL) of nifedipine (internal standard) was added to blank human plasma, and a single step extraction was carried out with ethyl acetate. The mixture was centrifuged, ethyl acetate layer separated, dried and reconstituted with 100 μL of acetonitrile. Twenty microliters of this solution was injected into a reverse phase C-18 column using a mobile phase consisting of acetonitrile: 0.02 M potassium dihydrogen phosphate (pH 4.0) in the ratio of 60:40 v/v and the eluents were monitored at 239 nm. The method was validated for its linearity, precision and accuracy. The calibration curve was linear in the range of 5-150 ng/0.5 mL of plasma and the lower detection limit was 2.5 ng/0.5 mL of plasma. The intra- and inter-day variation was found to be less than 2.5% indicating that the method is highly precise. The mean recovery of nicardipine hydrochloride from plasma samples was 89.6±2.60%. The proposed HPLC method was applied for the estimation of nicardipine hydrochloride in human plasma after oral administration of an immediate release nicardipine hydrochloride capsule (dose 30 mg) to 6 adult male volunteers. There was no interference of either the drug metabolites or other plasma components with the proposed HPLC method for the estimation of nicardipine hydrochloride in human plasma. Due to its simplicity, sensitivity, high precision and accuracy, the proposed HPLC method may be used for biopharmaceutical and pharmacokinetic evaluation of nicardipine hydrochloride and its formulations in humans